Effect of optic disc–fovea distance on the normative classifications of macular inner retinal layers as assessed with OCT in healthy subjects. Issue 6 (12th August 2018) - Qiu, Kunliang; Chen, Binyao; Yang, Jianling; Zheng, Ce; Chen, Haoyu; Zhang, Mingzhi; Jansonius, Nomdo M
Abstract : Purpose: To determine the influence of the optic disc–fovea distance (DFD) on the normative classifications based on thickness measurements of macular inner retinal layers with spectral-domain optical coherence tomography (OCT) in healthy subjects. Methods: A total of 182 eyes from 182 healthy subjects were included (mean (SD) spherical equivalent −0.8 (1.9) dioptres). We performed macula and optic disc imaging with the Topcon 3D OCT 2000. The thickness of the macular inner retinal layers (macular retinal nerve fibre layer (mRNFL), ganglion cell-inner plexiform layer (GCIPL) and both combined (ganglion cell complex; GCC)) and the corresponding classifications based on the built-in normative database were recorded. The occurrence of an abnormal normative classification (occurrence of any thickness variable below the fifth percentile) was related to the DFD and other factors (axial length/refraction, optic disc area, fovea–disc angle, age, gender, image quality, visual field mean deviation and peripapillary retinal nerve fibre layer thickness), using logistic regression. Results: The mean (SD) DFD was 4.90 (0.29) mm. A greater DFD was associated with a higher percentage of abnormal normative classification in the OCT parameters describing the thickness of the mRNFL (OR (95%CI) per 0.1 mm increase in DFD: 1.30 (1.13 to 1.50), p<0.001), GCIPL (1.18 (1.02 to 1.38), p=0.023) and GCC measurement (1.29 (1.08 to 1.55), p=0.006). Conclusions: Eyes with a greater DFD are prone to false-positive classifications in the thickness assessment of the macular inner retinal layers. The thicknesses should always be interpreted in the context of DFD.